Osgood Schlatter's disease - A burst in young football players - Marcio Domingues (Montenegrin Sports Academy, 2013)
Football is the most popular sport in the world. Like any contact sport it is susceptible to various kinds of injuries. It is referred the link between methodology of training and the prevention of overuse injuries in youth as it relates to maladaptive sport programs. There is an increasing awareness to growth related conditions and the relation of musculoskeletal development and the onset of youth related conditions. This article examines one specific injury sustained by children and adolescents who play football, Osgood Schlatter disease, and the main mechanisms whereby such injury occur. The aethology is complex and the risk factors underpinning injury occurrence are considered, along with injury avoidance tactics.